The Role of VapoRub in the Treatment of Seasonal Allergies - Parthiban, KG.; Devi, M. Kalpana; Sangameswaran, B.; Kannayiram, S. (Journal of Neonatal Surgery, 2025)
Millions of people worldwide suffer from seasonal allergies, sometimes referred to as allergic rhinitis, which can cause a variety of upsetting symptoms such as sinus pressure, sneezing, coughing, and nasal congestion. The immune system's hypersensitive response to environmental allergens such pollen, dust mites, and mold spores causes these symptoms. In order to regulate the immune system or lessen inflammation, conventional treatments usually include decongestants, nasal corticosteroids, and antihistamines. However, especially during the busiest allergy seasons, many patients look for complementary therapies to reduce symptoms and enhance comfort. A well-known topical ointment that has long been used to treat colds and coughs, vaporub has become more and more well-liked as a supplemental treatment for respiratory ailments. Vaporub's aromatic ingredients, which are mostly made up of menthol, camphor, and eucalyptus oil, activate cold receptors in the throat and nasal passages, producing a chilling feeling that can lessen coughing and improve the sense of airflow. Vaporub offers surface-level symptomatic relief that can be used in conjunction with traditional treatments, even though it neither directly reduces inflammation nor addresses the underlying immunological response. This article explores the pharmacological characteristics of the main chemicals in Vaporub and explains how they work in connection to allergy symptoms. It also examines anecdotal stories and clinical data pertaining to its effectiveness in treating symptoms such post-nasal drip-induced cough, nasal congestion, and allergy-related sleep disruptions. Safety considerations are also included, including possible side effects, appropriate administration instructions, and use in elderly and pediatric groups. The article concludes by highlighting Vaporub's function as a supportive therapy in the management of allergies, stressing both its advantages and disadvantages when used in conjunction with a more thorough treatment strategy.